Apoptosis in ischemia/reperfusion injury of human renal allografts - Burns, A T; Davies, D R; McLaren, A J; Cerundolo, L; Morris, P J; Fuggle, S V (Transplantation, 1998)
Ischemia/reperfusion injury of human renal allografts has a number of clinically significant consequences. A number of mechanisms of ischemia/ reperfusion injury have been elucidated, and there is evidence that apoptosis may be a contributing factor. To examine immediate posttransplant events, fixed tissue sections from paraffin-embedded wedge biopsy specimens taken before and after reperfusion of human renal allografts were stained using terminal deoxytransferase-mediated dUTP nick-end labeling to detect the DNA fragmentation characteristic of apoptosis. Thirty-six pairs of pre- and postreperfusion biopsy specimens were examined, 11 from living-related donor renal transplants and 25 from cadaveric donor transplants. Quantitation of the terminal deoxytransferase-mediated dUTP nick-end labeling signal showed that significantly more apoptosis occurred in postreperfusion compared with prereperfusion biopsy specimens from cadaveric donor transplants, but a similar difference was not observed in living-related donor renal transplants. Furthermore, significantly more apoptosis was observed in postreperfusion biopsy specimens from cadaveric compared with living-related renal transplants. Postreperfusion biopsy specimens from kidneys that were cold preserved longer than 30 hr had a higher mean apoptosis score than those stored for less than 24 hr, but the result was not statistically significant. Thus, apoptosis occurs predominantly as a result of reperfusion after cold preservation of cadaveric donor renal allografts and provides additional information regarding the extent of ischemia/ reperfusion injury in an organ. The clinical value of this information remains to be determined.